Prevalence and co-infection of acute hepatitis A virus and hepatitis E virus infections in patients with acute viral hepatitis - Daheriya, Hema; Gajbhiye, Sunita; Shrikhande, Sunanda (International Journal of Research in Medical Sciences, 2025)
Background: Viral hepatitis constitutes a significant global health burden, with hepatitis A virus (HAV) and hepatitis E virus (HEV) causing approximately 1.34 million deaths annually. This study aimed to determine the prevalence of acute HAV and HEV infections, evaluate co-infection patterns, and assess liver dysfunction among suspected acute viral hepatitis cases. Methods: This cross-sectional study was conducted from July 2023 to July 2024 at a tertiary care hospital. A total of 165 patients with clinically suspected acute viral hepatitis were included. Serum samples were tested for IgM antibodies against HAV and HEV using ELISA. Clinical severity was assessed using standardized grading criteria. Results: Among 165 patients with suspected acute viral hepatitis, HAV IgM seropositivity was 23.6% (39/165), HEV IgM seropositivity was 10.9% (18/165), and co-infection rate was 2.4% (4/165). HAV mono-infections comprised 21.2% (35/165) and HEV mono-infections 8.5% (14/165). Co-infected patients were significantly younger (mean age 15.8±4.2 years) compared to HAV (30.2±13.8 years) and HEV (25.6±11.4 years) mono-infections (p=0.042). Severe disease occurred in 50% of co-infected patients compared to <9% in mono-infections. Seasonal clustering was highly significant (p < 0.001) with 47.2% of cases during monsoon period. Conclusions: This study demonstrates significant HAV and HEV disease burden with young adults being most susceptible. Co-infected patients showed more severe clinical presentation requiring enhanced monitoring. Seasonal clustering emphasizes the environmental influence on transmission patterns.